EARNINGS MANAGEMENT TO ACHIEVE BENCHMARK TARGETS: A CASE OF SERBIAN LISTED COMPANIES - Marai, Awidat; Pavlovic, Vladan; Knezevic, Goranka; Almahrog, Yousf (Management Control Review, 2020)
The aim of this study is to investigate whether and how Serbian companies manage earnings to avoid losses and to avoid earnings decreases. The empirical evidence found in this study shows that there is a discontinuity in the distribution of reported earnings around the zero earnings benchmark suggesting that Serbian companies engage in earnings management to avoid reporting losses. Furthermore, this continuity disappears when we subtracted discretionary accruals from reported earnings indicating that Serbian companies use discretionary accruals as a tool for earnings management. However, the distribution of earnings does not provide evidence that Serbian companies manage earnings to avoid earnings decreases. These results are robust to alternative methods of scaling earnings and various ways of estimating discretionary accruals.